2022
DOI: 10.3390/ani12172250
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acacia Mearnsii Fodder on Rumen Digestion and Mitigation of Greenhouse Gas Production

Abstract: In recent years, the worrying generation of GHG from ruminant production has generated widespread interest in exploring nutritional strategies focused on reducing these gases, presenting the use of bioactive compounds (tannins) as an alternative in the diet. The aim of this research was to determine the effect of the addition of different levels of Acacia mearnsii on ruminal degradation, nutrient digestibility, and mitigation of greenhouse gas production. A completely randomized design with four treatments and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…The ruminal pH evidenced in the present study (Table 1) is consistent with that reported by Vargas-Ortiz et al [25], who consider positively benefit the activity of microorganisms that degrade cellulose.…”
Section: Gas Ch 4 Production and Rumen Phsupporting
confidence: 93%
See 1 more Smart Citation
“…The ruminal pH evidenced in the present study (Table 1) is consistent with that reported by Vargas-Ortiz et al [25], who consider positively benefit the activity of microorganisms that degrade cellulose.…”
Section: Gas Ch 4 Production and Rumen Phsupporting
confidence: 93%
“…To such an extent that negative effects on productive performance, feed consumption, digestion and animal health have been evidenced. Effects that are probably attributed to: (i) interaction of CT with salivary glycoproteins and subsequent decrease in feed palatability, (ii) greater permanence of feed in the rumen as a consequence of decreased substrate digestibility, (iii) intoxication by the excessive consumption of CT (>55 g CT/kg DM) and (iv) reduced intestinal enzymatic activity of trypsin, amylase and amino acid synthesis [25].…”
Section: Introductionmentioning
confidence: 99%
“…This is evidenced in the decrease in ruminal degradation and digestion in this study in diets T1 and T2. Vargas-Ortiz et al [ 33 ] and Kozloski et al [ 51 ], also found low digestibility when incorporating CT from A. mearnsii as forage and extract, respectively. The greater in situ degradation and in vitro digestibility of DM, evidenced in the present study, is probably due to the absence (T1: 0%) or low content of tannins in the diet (T2: 3% CT), that is an amount less than 5% of tannins [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, using Acacia mearnsii as forage for ruminants is a valuable alternative due to its wide distribution around the world and its ability to adapt to temperatures between 14.7–27.8 °C, as well as for presenting considerable quantities of bioactive compounds, mainly CT (35% to 45%), due to the antimethanogenic effect that this compound can provide [ 33 ]. Previous research has shown variability in the tannin effects on ruminal fermentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation